Poetic language and poetry - Petöfi, Janos S. (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article has three aims. The first aim is to give a terminological micro-analysis concerning the terms "poetic language" and "poetry". The second aim is to explain the distinction between the analytic-creative and the creative-productive approach defined in the theoretic framework of the semiotic textology. The creative-productive approach has the function, on one hand, to render the participants of the exercises more conscious for the analytic work and, on the other hand, to fumish a global view about the systetnic knowlegde these participants have concerning the analyzed aspects. The third aim is to demonstrate -with help of the exercises- the central aspects of the textological analysi5 of every type of texts.